@jake1010,
I'm not going to post a full proof, mainly because I can't be bothered, but also, I only know Gentzen-like proof systems, which I can't really post on a forum.
Start by using the disjunction elimination on ((~ T v Q) v R). So, now you need to prove (T & P) -> Q from both R and (~ T v Q).
To prove it from R, easy. From, R and the premise R -> ~P, get ~P. Now, assume (T & P) and get P. From the contradiction get Q, and use the conditional intro to get (T & P) -> Q and discharge your assumption.
To prove it from (~ T v Q) you're going to have to use the disjunction elimination again, so you will have to prove (T & P) -> Q from both ~T and Q. You should be able to prove (T & P) -> Q from Q without my help. To prove it from ~T, assume (T & P) from which you can get T. Use the contradiction to get Q, and then use the conditional into to get (T & P) -> Q and discharge your assumption.
You should be able to use the two uses of disjunction elim to discharge all of the other assumptions (of ~ T v Q, R, ~T, and Q).